PENGARUH PENERAPAN MODEL KELOMPOK BELAJAR TERHADAP PENAMBAHAN PENGETAHUAN PADA ORGANISASI PEMBELAJAR - , Lani Sukma Imtihani Djumasa ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to find out the influence of study team for knowledge acquisition to some employees of one of work unit in PT. Pupuk Kalimantan Timur. Prior to be devided into experiment and control groups at random, conducted matching process based on result of wiring diagram reading test. Experiment group (four subjects) is included to study team and discuss the topic about wiring diagram for four meeting. Prior and post study team meeting, subject given knowledge acquisition scale and wiring diagram problem. Control group (four subjects) asked to fulfill the knowledge acquisition scale and wiring diagram problem without included in study team. The analysis result with Man Whitney Test shows that the implementation of study team significantly able to enhance the knowledge acquisition to experiment group (pre test, sig (2-tailed)>0.05 and post test sig (2- tailed)<0.05). From wiring diagram processing, there is total score obtained by experiment group (score of pre test KE 31, KK 28 and score of post test KE 71, KK 51)